1998
DOI: 10.1076/ceyr.17.3.238.5222
|View full text |Cite
|
Sign up to set email alerts
|

Localization of TIMP-1, TIMP-2, TIMP-3, gelatinase A and gelatinase B in pathological human corneas

Abstract: These data suggest that TIMP-1 and TIMP-2 are important for scar formation and corneal remodeling, since they were found in increased amounts at radial keratotomy incision sites and keratoconus scars. The significance of the focal stromal defects in TIMP-3 staining, associated with absence of Bowman's layer on keratoconus corneas, needs to be elucidated. At the stages of disease examined in this study, gelatinase B may not play a significant role in these pathological processes, since it was not seen in any of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
9

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 44 publications
(53 reference statements)
1
48
0
9
Order By: Relevance
“…In keratoconus, stromal areas adjacent to regions where Bowman's layer was disrupted also stained for MDA. Because these regions are also associated with fibrosis (Kenney et al 1998(Kenney et al ,2000(Kenney et al ,2001, MDA staining may represent an association with fibrosis in the cornea.…”
Section: Malondialdehyde (Mda)mentioning
confidence: 99%
“…In keratoconus, stromal areas adjacent to regions where Bowman's layer was disrupted also stained for MDA. Because these regions are also associated with fibrosis (Kenney et al 1998(Kenney et al ,2000(Kenney et al ,2001, MDA staining may represent an association with fibrosis in the cornea.…”
Section: Malondialdehyde (Mda)mentioning
confidence: 99%
“…[1][2][3] In the normal cornea, only very low levels of MMP-2 are found as proenzyme. [4][5][6] After injury, and in response to the release of cytokines, several MMPs in the cornea are upregulated by transcription or activation. 7 Preformed MMP-9 (Gelatinase B) may also be released from the secretory granules of neutrophils recruited by any associated inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, studies with MMP mutant mice have confirmed that MMPs play an important role in promoting inflammation and immunity: overexpression of MMP-1 in lungs promotes a spontaneous emphysema-like response (6), MMP-12 loss attenuates macrophage migration and lung damage caused by cigarette smoke (27), MMP-7 participates in proteolytic activation of antibacterial defensins by epithelial cells (32) and chemoattraction of inflammatory cells to the lung (16), and MMP-3 loss diminishes T-cell-dependent delayed type hypersensitivity responses, while the loss of MMP-9 delays the resolution of those responses (30). TIMP expression has also been associated with a variety of infectious and noninfectious inflammatory conditions, including those affecting the eye (12,14,34), and TIMP-3 regulates tumor necrosis factor alpha (TNF-␣) production (18). Collectively, these data highlight varied and complex roles for components of the TIMP-MMP axis during immune and inflammatory responses; however, TIMPs have not been directly shown to regulate responses to infection.…”
mentioning
confidence: 99%